Respiratory Care - Duncan, Deborah (M & K Update Limited, 2017)
This helpful book looks at the respiratory problems that nursing and healthcare professionals are most likely to encounter in clinical practice. Beginning with an overview of the respiratory system, the author then discusses history taking, and the physical assessment and secondary tests needed to assess a patient with an undiagnosed respiratory condition. This is followed by chapters on the aetiology, assessment and management of specific acute and chronic conditions, as well as a chapter on the pharmacology of respiratory disease. Finally, the author looks at intermediate, home-based and end.